Afterimage watercolors: an exploration of contour-based afterimage filling-in - Hazenberg, Simon Jan; van Lier, Rob (Frontiers in Psychology, 2013)
We investigated filling-in of coloured afterimages and compared them with filling-in of ‘real’ colours in the watercolour illusion. We used shapes comprising two thin adjacent undulating outlines of which the inner or the outer outline was chromatic, while the other was achromatic. The outlines could be presented simultaneously, inducing the original watercolour effect, or in an alternating fashion, inducing coloured afterimages of the chromatic outlines. In Experiment 1, using only alternating outlines, these afterimages triggered filling-in, revealing an ‘afterimage watercolour’ effect. Depending on whether the inner or the outer outline was chromatic, filling-in of a complementary or a similarly coloured afterimage was perceived. In Experiment 2, simultaneous and alternating presentations were compared. Additionally, grey and black achromatic contours were tested, having an increased luminance contrast with the background for the black contours. Compared to ‘real’ colour filling-in, afterimage filling-in was more easily affected by different luminance settings. More in particular, afterimage filling-in was diminished when high-contrast contours were used. In the discussion we use additional demonstrations in which we further explore the ‘watercolour afterimage’. All in all, comparisons between both types of illusions show similarities and differences with regard to colour filling-in. Caution, however, is warranted in attributing these effects to different underlying processing differences.